La medición del contrabando de cigarrillo en Colombia entre 1990 y 2012 (2013)
Illegal trade flow has existed in Colombia since the 18th century, including trade of tobacco and its products. The government has developed policies and laws with the purpose of curbing this phenomenon. However, the country has not implemented a measuring method to estimate illicit commerce and thus, has not been able to develop evidencebased policies. On the other hand, today Colombia should adopt existing international protocols, methodologies, and agreements, to ensure adequate action coordination across the Latin American region and improve efficiency in the control of illicit tobacco flows. The purpose of this paper is to identify and compare studies and methologies used to measure cigarette smuggling worldwide in order to use these techniques in a Colombian case study, and to confront these methodologies with some estimations elaborated in documents produced in the country.